TRANFROMASI MANAJEMEN KASUS : RESTRUKTURISASI ORGANISASI DIPLOMAI III PROGRAM STUDI USAHA WISATA MENJADI S1 PARIWISATA - Suharyono Suharyono; Rebin Sumardi (Jurnal Ilmu dan Budaya, 2019)
The development of the tourism industry should be supported by skilled human resources, these resources can be printed from the high schools of tourism that prepare educators with the provision of science in accordance with industry demands. Improving the quality of education is something that must be done so that we are able to compete with foreign graduates by producing competent and professional learners. Improvement of quality improvement of high school especially high school of tourism can be done by organizational reform. This research explores. Organizational changes at the National Academy of Tourism academy institutions so that the library still exists and maintains the quality of its education so that its graduates meet the industry's qualification standards.